Aquarian Kill, Followed by a Brief Prayer - Jordana A., Evra (Satura, 2022)
I. Throw me on like clean laundry and I will drink you until we both can’t breathe. A deal between Rahu and Ketu. Between your hips and my tongue. Fucking spit me out. Stitch my name into the fraying seams of the prayers you fumble to speak, as purple cuts this mourning sky. Use me before God. Tell him I was dreadfully happy to undress you like dessert after dinner. I want you to come to me. Find me. Don’t kiss me. Possess me. Take my ringing heart in your tired hands and let’s work something out. But first, we fuck.